The influence of stakeholder engagement practices in faecal sludge management system in Embu County - Mugendi, Cyrus (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
General information Global fecal sludge management heavily relies on on-site sanitation, with 1.3 billion out of 2.7 billion people depending on it, especially in urban areas where urban poor and peri-urban residents face increased risks but are often overlooked. Access to sanitation in urban areas globally is estimated between 65 and 100 percent. This study assessed the impact of stakeholder engagement on fecal sludge management practices in Embu County Study methods. A sample size of 157 respondents, comprising of managers, technicians, contractors, people involved in exhausting, and landlords, using a combination of primary and secondary data. Questionnaires and interview were used to gather qualitative and quantitative data, and the Cronbach alpha method assessed reliability. Results The findings indicated that stakeholder engagement also had a significant positive effect on implementation, with a one-unit increase resulting in a 0.355-unit increase in system implementation. The mean score of 5.00 signifies complete agreement among the stakeholders in prioritizing alignment with the community’s needs. The standard deviation of 0.00 further emphasizes this unanimity, indicating that all stakeholders place great importance on selecting projects that address the specific requirements and concerns of the community. Finally, 57.2% of the effects of the predictors on the sustainability of community sanitation projects as represented by the R2which means that other factors not studied in this research contribute 42.8% of the effects of the independent variables on implementation fecal sludge management Conclusion and recommendations In conclusion, successful fecal sludge management requires proper resource planning, active stakeholder engagement, and robust Monitoring and Evaluation. Decision-makers should prioritize allocating appropriate resources, engaging stakeholders, and establishing comprehensive monitoring mechanisms. These measures will improve sanitation practices, reduce environmental impacts, and enhance public health and sustainable development. Recommendations include developing a comprehensive involvement stakeholder at all levels, investing in capacity building and training, and raising public awareness of responsible waste disposal. These actions will help ensure the successful implementation of fecal sludge management systems, particularly in Africa and Kenya, where proper sanitation practices are crucial for public health and environmental protection. The study emphasizes the pivotal role of stakeholder engagement in the success of fecal sludge management and highlights areas for improvement to enhance effectiveness.